GEOCHEMICAL VARIATIONS ON HOSTED VOLCANIC ROCKS OF CIBALIUNG EPITHERMAL GOLD MINERALISATION, BANTEN – INDONESIA: IMPLICATIONS FOR DISTRIBUTION OF SUBDUCTION COMPONENTS - Anastasia Dewi Titisari; David Phillips; Hartono Hartono (Geological Engineering Department Universitas Gadjah Mada, 2015)
Subduction of the Indo-Australian Plate beneath the Eurasian Plate formed at least seven magmatic arcs in Indonesia. One of the magmatic arcs is the Neogene Sunda-Banda arc hosts various style of gold mineralisation such as Cibaliung epithermal gold mineralisation. Major and trace element data for host volcanic rocks to the Cibaliung epithermal gold mineralisation is provided by this study to identify the magmatic arc system and the distribution of subduction components. Enriched LILE (Large Ion Lithopile Element) and LREE (Light Rare Earth Element) compositions for basaltic andesite – rhyodacitic samples from the Cibaliung district are characteristic of calc-alkaline arcs. In this typical volcanic arc, the subduction component can be shown to make a dominant contribution to its content of LILE such as Rb, K, Th, and Ba enriched (more than 88%) relative to the mantle and within plate inputs. The incompatible elements (Hf, Zr, and Nb) cannot be observed in the subduction component and thus assumed to be derived from trace element enriched sub-continental lithosphere. These incompatible elements are defined as conservative elements therefore it suggests that the magma occurrence is related to a hydrous slab component. Keywords: Subduction, Indo-Australian plate, magmatic arcs, volcanic rocks, Cibaliung, epithermal gold.